Structural processes of management and conservation of wildlife at risk of extinction: Amazonian cases (Sustainability in Debate, 2018)
The present work analyzes the structure and processes involved in the conservation and management of two species of the Amazonian wild fauna in danger of extinction. The research approached the context of the conservation programs of the Harpy eagle (Harpia harpyja) and the yellow-spotted Amazon river turtle (Podocnemis unifilis) developed within interior communities of the state of Amazonas. The research was based on a documentary research with content analysis. The analyzes allowed to agglutinate processes and strategies involved in the conservation of these two flagship species, based on participatory community management. It has been found that conservation practices for both species are distinct but indicate common and propositional dimensions such as participation, collaboration, communication and education.